MUNICH CRISIS: BEHIND – THE SCENE HISTORY - A. Y. Borisov (MGIMO University Press, 2017)
The article links the tragic historical past of Czechoslovakia, which paid its price for the rejection of sovereignty as a result of its elite’s national policy, with the current political discourse around globalization and national interests, the influence of external forces on the policies of dependent states, and often the negative consequences of this influence. Much of today’s policies of the leading Western powers, primarily the United States, echo their actions during the preparation and implementation of the Munich conspiracy. Playing on international contradictions while staying aside, turning in a victim to an aggressor, etc. are dangerous policies both in the past and today and lead to serious international consequences for their organizers and inspirers. Unlike numerous works on this subject, which have appeared in Russia and abroad, focusing mainly on the activities of European «appeasers», the author of the article shows the hidden role of American diplomacy in deciding the fate of Czechoslovakia. The US was headed by President Franklin Roosevelt – an acknowledged master of the game on international controversies, avoiding being on the foreground of world politics on dubious issues. To clarify the role of the US in European politics during the Munich crisis, the article draws on original sources from the archive of the American ambassador to the Soviet Union, J. Davis from the Library of Congress.